ANALISIS LIKUIDITAS, SOLVABILITAS DAN KEBIJAKAN DIVIDEN DAPAT MENINGKATKAN NILAI PERUSAHAAN PADA PT KEBELINDO MURNI,Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pardede, Demak Aldi; Jubi, Jubi; Inrawan, Ady; Putri, Juan Anastasia (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The purpose of this study are: 1. To find out an overview of liquidity, solvency, dividend policy and company value in PT Kabelindo Murni, Tbk, which is listed on the Indonesia Stock Exchange. 2. To find out what factors cause company value in PT Kabelindo Murni, Tbk to increase.               The author's research was conducted using qualitative descriptive analysis techniques, comparative analysis techniques and inductive analysis techniques. The type of data in the study are qualitative data and quantitative data. The data source used is secondary data. Data collection in research is documentation techniques.               The results of this study concluded 1. The average value of liquidity with the parameter Current Ratio (CR) fluctuates and tends to increase, but the increase in current assets was followed by an analysis with a decrease in the value of current liabilities. 2. The average solvency value with the parameters Debt to Asset Ratio (DAR) fluctuates and tends to decrease, this is due to a decrease in debt which is higher than the decrease in the total assets of the company. 3. Dividend Policy (DPR) experienced fluctuations and tended to increase. This was caused by an increase in dividends per share while there was a decrease in earnings per share. 4. The company value with PBV parameters fluctuates and tends to increase, this is due to an increase in stock prices higher than the increase in book value per share.               Suggestions for this research are: It is better for companies to add working capital by making long-term debt to buy inventory that can increase sales, it is best for companies to increase sales and reduce operating expenses so that profits can increase and increasing profits can increase EPS so that the DPR can be controlled, it is best for companies to increase profits by increasing sales and streamlining operating expenses. Increasing profit can be used as working capital of the company. Keywords : Liquidity Analysis, Solvability, Dividend Policy and  Company Value